TINAJUAN TENTANG KUALITAS PELAYANAN DI RESTORAN SATOO HOTEL HW PADANG - Saputra, Jeri; Kasmita, Kasmita; Abrian, Youmil (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This study aims to determine the Quality service in satoo restaurant HW Hotel Padang. This type of research is descriptive quantitative. Population of this research amounting to 255 person. The technical take of sampling using purposive sampling amounting 72 person. Collecting data using a questionnaire based on Likert Scale which has proven its validity and reliability. The results showed that overall quality service belong to a category good enough with the average value of 3,06 which were in the range 2,61-3,40. While based on individual indicators is: reliability, responsiveness, assurance, and tangibles belong to a category good enough in range 2,61-3,40. while empathy belong to a category good with the average value of 3,82 in range 3,41-4,20.